KEDUDUKAN OBJEK AKAD SEBAGAI AKIBAT HUKUM PERJANJIAN (KAJIAN REFLEKTIF DALAM FIKIH MUAMALAH) - Nilam Sari, Devi (Islamic Banking & Economic Law Studies (I-BEST), 2024)
This article explores the legal implications of the object within various agreements in the context of fiqh muamalah. As muamalah activities grow increasingly complex, it becomes crucial to regularly assess the validity of these agreements and the legal consequences that arise from them. This research adopts a normative approach to Islamic law, utilizing secondary data gathered through library research and employs a descriptive analytical method. In evaluating the position of the contract object and its legal consequences, it is essential to first interpret the scope of the agreed terms. This involves determining the extent to which the contract is binding, and whether the terms of the contract have been fulfilled as agreed. The consequences stemming from the object are also examined through the concept of Aman al-aqd, which addresses the responsibilities arising from a failure to execute the contract. This exploration provides a deeper insight into the legal mechanisms that govern the binding nature of agreements in Islamic law.